1994
DOI: 10.1073/pnas.91.8.3181
|View full text |Cite
|
Sign up to set email alerts
|

Formation of in vivo complexes between the TAL1 and E2A polypeptides of leukemic T cells.

Abstract: Tumor-specific activation of the TALI gene occurs in "r.25% of patients with T-cell acute lymphoblastic leukemia (T-ALL). The TALI gene products possess a basic helix-oop-belix (bHLH) domain that interacts in vitro with the bHLH proteins (E12 and E47) encoded by the E2A locus. We have now applied two independent methods, the two-hybrid procedure and co-immunoprecipitation analysis, to demonstrate that TALl and E2A polypeptides also associate in vivo.These studies show that the bHLH domain of TALl selectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 39 publications
(52 reference statements)
2
99
0
Order By: Relevance
“…In T-lymphocytes, E2A interacts with HEB, a member of the Class I bHLH family and activates target genes, whereas in Blymphocytes, E2A functions through the formation of a homodimer to regulate downstream genes (Lazorchak et al, 2005;Murre, 2005). As LYL1 can also interact with E2A (Hsu et al, 1994;Xia et al, 1994;Miyamoto et al, 1996), we asked whether ectopic overexpression of LYL1 had any effect on E2A dimerization. By using a mammalian two-hybrid system, we found that LYL1 interacted with E2A although this interaction was weaker than that of E2A-HEB ( Figure 4a).…”
Section: Overexpression Of Lyl1 Induces Malignant Lymphomamentioning
confidence: 98%
See 1 more Smart Citation
“…In T-lymphocytes, E2A interacts with HEB, a member of the Class I bHLH family and activates target genes, whereas in Blymphocytes, E2A functions through the formation of a homodimer to regulate downstream genes (Lazorchak et al, 2005;Murre, 2005). As LYL1 can also interact with E2A (Hsu et al, 1994;Xia et al, 1994;Miyamoto et al, 1996), we asked whether ectopic overexpression of LYL1 had any effect on E2A dimerization. By using a mammalian two-hybrid system, we found that LYL1 interacted with E2A although this interaction was weaker than that of E2A-HEB ( Figure 4a).…”
Section: Overexpression Of Lyl1 Induces Malignant Lymphomamentioning
confidence: 98%
“…Similar to LYL1, sustained expression of TAL1/2 owing to chromosomal translocation is associated with a T-cell leukemia/lymphoma (Xia et al, 1991;Begley and Green, 1999). Both LYL1 and TAL1/2 proteins can interact with Class I bHLH proteins (Hsu et al, 1994;Xia et al, 1994;Miyamoto et al, 1996) and LIM-domain-only (LMO) proteins through their bHLH motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, heterodimer formation is essential for the DNA-binding activity and functional properties of these proteins. A stable tal-1/E2A complex has been detected in Jurkat cells (Hsu et al, 1994b). However, it remains unclear whether this complex is a consistent feature associated with tal-1-induced leukemia.…”
Section: Tal-1r188g;r189g Thymomas Do Not Express Cd4mentioning
confidence: 99%
“…In human leukemic Jurkat cells, tal-1 does not homodimerize, but forms stable heterodimers with the ubiquitously expressed bHLH E2A proteins, E12 and E47 (Hsu et al, 1994b). Members of the E2A family include E2-2, HEB and the products of the E2A gene E47 and E12 (Murre et al, 1989;Henthorn et al, 1990;Hu et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a full-length protein (pp47 TAL1 ), which has been detected in essentially all cells that transcribe the gene (Cheng et al, 1993;Hsu et al, 1994b), an amino-terminally truncated protein (pp24 TAL1 ) generated through alternative splicing has been observed in human and murine leukemia cell lines (Cheng et al, 1993;Hsu et al, 1994b) and Friend virus-induced proerythroblasts (Prasad et al, 1995). This shorter isoform is also the sole TAL1 species expressed in leukemias with the rare SIL-TAL1 d 3 deletion (Bash et al, 1993).…”
Section: Introductionmentioning
confidence: 99%